2003
DOI: 10.1093/jnci/djg084
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopic Pharmacodynamic Markers of the Heat Shock Protein 90 Inhibitor 17-Allylamino,17-Demethoxygeldanamycin (17AAG) in Human Colon Cancer Models

Abstract: Inhibition of Hsp90 by 17AAG resulted in altered phospholipid metabolism in cultured tumor cells and in tumor xenografts. The increases observed in phosphocholine and phosphomonoester levels suggest that these metabolites may have the potential to act as noninvasive pharmacodynamic markers for analyzing tumor response to treatment with 17AAG or other Hsp90 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 49 publications
10
82
2
Order By: Relevance
“…As expected, inhibition of HIF-1a with PX-478 led to a trend of decreased glucose uptake and lactate production in HT-29 tumour xenografts (Jordan et al, 2005). Furthermore, inhibition of HSP90 with 17-AAG in HT-29 xenografts resulted in a moderate drop in NTPs (Chung et al, 2003), and blockade of HDAC in the same model with LAQ824 resulted in dramatic decreases in PCr, NTP and glucose levels and increased Pi. However, the effects reported, at least in the case of LAQ824, were likely to result from the induced anti-angiogenic effects and the accompanying increase in tumour necrosis .…”
Section: Choline Phospholipid Metabolismsupporting
confidence: 66%
“…As expected, inhibition of HIF-1a with PX-478 led to a trend of decreased glucose uptake and lactate production in HT-29 tumour xenografts (Jordan et al, 2005). Furthermore, inhibition of HSP90 with 17-AAG in HT-29 xenografts resulted in a moderate drop in NTPs (Chung et al, 2003), and blockade of HDAC in the same model with LAQ824 resulted in dramatic decreases in PCr, NTP and glucose levels and increased Pi. However, the effects reported, at least in the case of LAQ824, were likely to result from the induced anti-angiogenic effects and the accompanying increase in tumour necrosis .…”
Section: Choline Phospholipid Metabolismsupporting
confidence: 66%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] Increasing evidence has shown that specific inhibition of HSP90 in neoplastic cells can lead to cell cycle arrest and apoptosis. [8][9][10][11][12][13][14][15][16][17][18][19][20] No previous study, however, has systematically surveyed HSP90 expression in a variety of NHL types as defined in the WHO classification. Thus, the aim of this study was to assess for HSP90 expression in various types of B-and T-NHL, in light of the potential utility of HSP90 inhibitors in the treatment of patients with NHL.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recently, in vitro studies have shown that treatment of solid tumors and hematological malignancies with a naturally occurring antibiotic, geldanamycin, and its derivative, 17-AAG, inhibits HSP90 activity through blocking ATP-binding sites of the HSP90-partner complex, with subsequent proteosomal degradation and/or dephosphorylation of client proteins. [10][11][12][13][14][15][16][17][18][19][20] These HSP inhibitors act mainly by occupying the binding site for the client protein within the HSP90-multichaperone complex and, by blocking this step, these derivatives enhance protein destabilization with subsequent shortening of protein half-life and eventual proteosomal degradation. 9 Based on the promising results of preclinical studies, [10][11][12][13][14][15][16][17][18][19][20] several phase I clinical trials with 17-AAG have been initiated in the United States and United Kingdom for patients with hematological malignancies, and solid tumors including breast, prostate and kidney cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, treatment with heat shock protein 90 or histone deacetylase inhibitors in human colon and prostate carcinoma cells lead, interestingly, to an increase in the phosphocholine and phosphomonoester signal (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%